1985
DOI: 10.1210/jcem-60-2-294
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Urinary 5a-Androstane-3α,17β-Diol Glucuronide Excretion in Patients with Benign Prostatic Hyperplasia*

Abstract: Urinary testosterone and 3 alpha-androstanediol (3 alpha diol G) glucuronides together with plasma testosterone, 5 alpha-dihydrotestosterone (DHT), and delta 4-androstenedione (delta 4) were measured in 43 normal young men (18-36 yr old), 23 elderly men without clinically evident prostatic pathology (54-89 yr old), 68 elderly men with benign prostatic hyperplasia (BPH group; 54-91 yr old), and 26 elderly men with well differentiated cancer of the prostate (K group; 63-97 yr old). Plasma testosterone decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
2
8
1
Order By: Relevance
“…Some other urinary steroids quantified were also significantly different in patients and controls (P Ͻ 0.01). Changes in the urinary levels of ␣␣␤-diol and ␣␤␤-diol were in accord with previous findings [36,37], but other steroid changes observed in this study have not been reported to date. In particular, urinary 17␤-E2 and 2-OH-E3 showed remarkable changes with P values of 2.77 ϫ 10 -13 and 4.25 ϫ 10 -9 , which might be associated with the different biochemical roles of estrogen receptor ␣ (ER␣) and ␤ (ER␤) in various types of prostate cells [28,38,39].…”
Section: Quantitative Results Of Benign Prostatic Hyperplasiasupporting
confidence: 92%
“…Some other urinary steroids quantified were also significantly different in patients and controls (P Ͻ 0.01). Changes in the urinary levels of ␣␣␤-diol and ␣␤␤-diol were in accord with previous findings [36,37], but other steroid changes observed in this study have not been reported to date. In particular, urinary 17␤-E2 and 2-OH-E3 showed remarkable changes with P values of 2.77 ϫ 10 -13 and 4.25 ϫ 10 -9 , which might be associated with the different biochemical roles of estrogen receptor ␣ (ER␣) and ␤ (ER␤) in various types of prostate cells [28,38,39].…”
Section: Quantitative Results Of Benign Prostatic Hyperplasiasupporting
confidence: 92%
“…The metabolite 5␣-androstane-3␣,17␤-diol (3␣-diol), which is converted by 3␣-hydroxysteroid dehydrogenase from DHT, has been considered another active androgen and a potential causative agent of BPH (3,4,11 ). In the present study, its glucuronide was not measured because 3␣-diol is reversibly converted to DHT (12 ).…”
mentioning
confidence: 93%
“…The method described here simplifies the procedure to a two-stage PCR amplification and allows the probe sequence to be placed anywhere between the primer binding sites without the need to identify or engineer restriction sites. Similar approaches have been described previously (3)(4)(5), although none of these is as simple or universally applicable as the method described here. As an example, the method has been used to synthesize a molecular construct for use as an internal standard in a quantitative PCR method for measles virus (MV) RNA.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Like the high-temperature GC-MS method, CE-MS/MS method needs no derivatization or sample preparation for solid-phase extraction, and small volumes of sample and solvent can be used. Because the measurement of urinary androgen glucuronides could demonstrate clinical implications with increased DHT in plasma and tissue (Wilson, 1980;Wright et al, 1985), and decreased DHT-17G in urine (Choi et al, 2003) in patients with BPH, determination of urinary androgen glucuronides without deconjugation is very useful technique.…”
Section: Application To the Urine Samplesmentioning
confidence: 99%